DEVELOPMENT OF CREATIVE ABILITIES OF PRESCHOOL CHILDREN THROUGH UNCONVENTIONAL METHODS - Turakulova Feruza, Karimnazarova Uzlifat (Journal Park Publishing, 2023)
This article presents methods for developing the creative abilities of preschool children from 3 to 7 years old through various non-traditional drawing methods.
Keywords: creativity, exploration, development, imagination, visual, traditional, unconventional, fantasy, hands, palms, fists.